Productive and economic description of a commercial cattle finishing system in the northern zone - Ellis-Calderón, Randy (2022)
The objective of this study was to describe and analyze the productive and economic performance of a commercial finishing cattle system under an intensive grazing scheme with strategic supplementation during the period between 2009 and 2016. The supplementation showed a positive impact when the bulls spend 183 days on the farm with a daily weight gain of 1,067 kg to 94 days with 1,871 kg; this reduction in farm increased the number of production cycles per year, from selling 112 animals in 2009 to 811 in 2016. Thus, the net profit per bull in 2009 increased from ₡31.410.19 to ₡52.618.33 in 2016. Finally, the profitability percentage was similar in the years evaluated, oscillating between 6% and 7%. It is concluded that strategic supplementation made a great improvement in the productive and economic performance of the production system.